Developmental Stability in Chickens Local to Warm Climate 1. Variation in Internal Organs and Bilateral Traits of Lines Selected Short-Term for Growth - El-Gendy, Essam A. (International Journal of Poultry Science, 2009)
This study aimed at adopting the developmental changes in the internal organs and bilateral traits of growing chickens selected five generations for increased 6-week body weight and genotyping for normal feathering (line F) or naked-necks (line N), compared to their corresponding genetic controls (lines CF and CN). Line N had the smallest weight percentages of total lungs and liver (0.54 and 2.38%) and biggest weight percentages of right and left shanks (2.46 and 2.48%). Line F had the smallest spleen weight percentage (0.20%) and tallest right and left shanks (8.50 and 8.57 cm) and widest right and left shanks (3.74 and 3.75 cm). Gizzard weight percentages of lines N and CN (3.37 and 3.55%) were significantly more than those of lines F and CF (2.74 and 3.00%). The results indicated that neither short-term selection nor Na allele have influenced the development of heart. Na allele showed variable pleiotropic effects, where the weight percentages of lungs and liver were decreased and the weight percentages of gizzard and spleen were increased. A reduction in lung and liver weight percentages characterized the naked-neck selected line, revealing an interaction between selection and Na allele. The pressure of short-term selection for body weight was early noticeable on the development of liver and spleen that could initiate possible metabolic disorders or susceptibility to disease infection later with the continuity of selection scheme. Short-term selection albeit boosted the bilateral shank measurements, but did not influence the bilateral developmental stability. The developmental stability characterized the bilateral characters in chickens carrying Na allele, suggesting a role of Na allele in the developmental stability of the birds pertaining the natural heating waves. The results of correlation coefficients indicated that the bilateral asymmetries of different characters are not significantly associated.